1977
DOI: 10.1172/jci108876
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the third component of complement (C3) in vitro by monocytes from both normal and homozygous C3-deficient humans.

Abstract: A B S T R A C T Human monocytes synthesized the third component of complement (C3) up to 5 wk in vitro. Evidence for net C3 synthesis was based on (a) incorporation of 14C-labeled amino acids into C3 protein, (b) identity of the allotype of C3 produced in vitro with that of the doner's serum C3, even in the presence of carrier C3 protein of a different allotype; (c) correspondence of electrophoretic mobility, size, and subunit structure of C3 protein produced in vitro with serum C3; (d) inhibition of C3 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 21 publications
(24 reference statements)
1
40
0
Order By: Relevance
“…Increasing evidence from in vivo as well as in vitro experiments has raised since, Bottger et al, 1986Ochs et al, 1983Pepys, 1974 Page / 2 11 ) and ii) they are known to secrete larger amount of C3 at sites of inflammation than other APC ( ). Our et al, Einstein et al, 1977 results constitute the first evidence that C3b can indeed inhibit lysosomal proteases. This inhibitory activity is specific of C3b and is supported by the C3c fragment.…”
Section: Introductionsupporting
confidence: 66%
“…Increasing evidence from in vivo as well as in vitro experiments has raised since, Bottger et al, 1986Ochs et al, 1983Pepys, 1974 Page / 2 11 ) and ii) they are known to secrete larger amount of C3 at sites of inflammation than other APC ( ). Our et al, Einstein et al, 1977 results constitute the first evidence that C3b can indeed inhibit lysosomal proteases. This inhibitory activity is specific of C3b and is supported by the C3c fragment.…”
Section: Introductionsupporting
confidence: 66%
“…In agreement with this, we demonstrated C3 mRNA in the cell lines examined (Supplemental Figure 6). Although most C3 is secreted, it has been shown that some cell types store C3, such as human neutrophils (36) and monocytes (37). The derivation and composition of these C3 stores have not been delineated.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, C2 and C4, which are also part of the CP, have been shown to be secreted by monocytes [26,28,[57][58][59]. Monocytes also secrete various AP components as C3, FB, FD and FP [24,[59][60][61][62][63][64]. Moreover, the terminal pathway components C5, C6, C7, C8 and C9 are secreted, which are able to assemble as MAC [24,65].…”
Section: Monocytesmentioning
confidence: 99%